Evaluation of mechanical performance on a developed AA 6061matrix-Mg/0.9-Si/0.68 reinforced with B4C based composites. (10th February 2021) - Singh, Hartaj; Singh, Gagandeep; Singh, Kapil; Vardhan, Sachit
Abstract: Aluminum matrix composites are chosen for electronic, aircraft, and automobile components due to the lightness of their weight and high specific strength. High-quality aluminum-based composites are well known for their microhardness and high refractoriness performance in aerospace with the advantage of structural applications. The boron carbide ceramic as a reinforcement plays an outstanding function in the base matrix to enhance the mechanical behavior of the composites. The present effort revealed that the synthesized composites were fabricated by the stir casting process and B4 C having a particulate size of 50 µ m were reinforced from 1% to 15% in the AA 6061 by varying weight percentages. Microhardness such as Brinell and Rockwell hardness moreover impact testing was performed experimentally. The mechanical characterization of fabricated composites with high mechanical performance-based composites has been investigated in this research work. Using microstructural characterization by scanning electron microscopy and x-ray diffraction we examinded high mechanical performance-based composites.